The Effects of Learning Activity Through Creativity-Based Learning with Macro Model of Learning Achievement in That Literature and Analytical Thinking Ability of Mathayom Suksa 1 Students. - Thungkham, Theerawat; Thiamtham, Thattharit; Lekvilai, Supawan (Saengtham College Journal, 2024)
The objectives of this research were to 1) Compare the Thai Literature’s learning achievement of Mathayomsuksa 1 students after learning by using Creativity-Based Learning with MARCO Model with the criteria of 70 percent 2) compare the analytical thinking ability of Mathayomsuksa 1 students before and after learning and 3) Study the Mathayomsuksa 1 students’ opinions on the teaching and learning approach. The samples of this research were 50 Mathayomsuksa 1 students of Saint Theresa School which were selected by using cluster sampling. The research instruments were Assessment form of the teaching and learning process, Lesson plans of Creativity-Based Learning with MARCO Model – Topic: Karb Phrachaisuriya, Achievement test, Analytical thinking test, Opinion questionnaire of students towards the teaching and learning. The statistics used to analysed data were percentage, mean, standard deviation (S.D.), one sample t-test and dependent sample t-test. The results were found that Thai Literature’s learning achievement of Mathayomsuksa 1 students after learning by using Creativity-Based Learning with MARCO Model was higher than the criteria of 70 percent with statistically significant at .05 level. The analytical thinking ability of Mathayomsuksa 1 students after learning by using Creativity-Based Learning with MARCO Model higher than before learning with statistically significant at .05 level. And the overall opinion of Mathayomsuksa 1 students toward learning by using Creativity-Based Learning with MARCO Model was at the highest level.